Solvent-assisted cavitation for enhanced removal of organic pollutants - degradation of 4-aminophenol - Patil, Pravin B.; Bhandari, Vinay M. (Journal of Environmental Management, 2022)
A new approach of solvent-assisted cavitation process was proposed for degradation of organic pollutants. The process envisages the use of suitable solvent as an additive, (1-5% v/V), in the conventional cavitation process to enhance the pollutant removal efficiency. A proof of concept was provided for the removal of ammoniacal nitrogen with significantly improved efficiency using solvent-assisted hydrodynamic cavitation (HC) compared to conventional HC. The efficacy of the process was studied on a pilot plant scale (1 m(3)/h) and using vortex flow based vortex diode as a cavitating device. Degradation studies were carried out using a model pollutant, 4-amino phenol and four different solvents as additives, 1-octanol, cyclohexanol, 1-octane and toluene. Relatively polar solvents were found to increase the efficiency of the pollutant removal (> 65%) and also increase the rates to an extent of more than 200%, compared to only HC. A very high removal of ammoniacal nitrogen, more than 90%, was obtained for solvents 1-octanol and cyclohexanol, indicating the importance of the selection of solvent. Per pass degradation model showed 3 to 4 times increase in the per pass degradation for polar solvents compared to cavitation alone. The results confirm no role of conventional solvent extraction and no specific contamination of wastewater due to the use of solvent as an additive in the process. Further, the cost was 2-3 times lower as compared to the conventional HC. The interesting observations in the proposed process can fuel further research to provide possible improvements in existing methodologies of wastewater treatment, in general, and for removal of ammoniacal nitrogen, in particular.
Keywords: Ammoniacal nitrogen; Hydrodynamic cavitation; Oxidation; Pollution Control; Wastewater treatment